The Investigation of Cracks and Repairing Methods on Residential Building: Case Study at Kompleks Penghulu Ayer Hitam, Muar - Tuan Norhayati Tuan Chik; Mas Ezaty Mohamad; Nor Aiza Erme Mohamad; Nor Athirah Farhah Mat Jali; Muhammad Azizi Yusri Rusidi (Journal of Structural Monitoring and Built Environment, 2024)
Malaysia is among one of the development countries that growing rapidly in all sectors which include the sector in construction. Nevertheless, some of the new buildings are poorly constructed. The aim of this study is to investigate the residential house wall cracks on the residential building at Kompleks Penghulu Ayer Hitam, Muar, to inspect the crack occurred on the residential building, to conduct a statically analysis to compare the relationship between ultrasonic pulse velocity and crack repair method and to propose efficient method for reducing the cracks problem. There are 52 number of visible cracks with different length and width has been detected. For measuring the concrete strength, a non-destructive testing (NDT) was used using Ultrasonic Pulse Velocity (UPV). The total 3 point was tested on column and wall inside the residential house by using one modes of transmission for UPV testing which was indirect transmission. The result of UPV has been analyse using statistical evaluation. From the result, it is found that the epoxy injection can cure the crack while seal using OPC and silicone seal does not help much. For overall cracking and concrete strength quality, it is also found that the residential building needs proper maintenance as the settlement still happened, and it is affected the residential building’s safety.